PENGAKUAN KEBERADAAN MASYARAKAT HUKUM ADAT SUKU SAKAI BATHIN SOBANGA KOTA DURI TAHUN 2022 - ', Lusianti; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
A customary law community is a group of people who are orderly and live in a certain area, no one among the members has the thought or inclination to dissolve the ties that have grown or leave or break away from those ties forever. Riau Province itself has various ethnic groups, approximately 285 indigenous communities have been identified and 17 MHA have received recognition, one of which is the Sakai Bathin Sobanga Tribe in Bengkalis Regency, Riau Province. The aim of this research is to determine the stages of recognition of the existence of MHA in the Sakai Bathin Sobanga Tribe and the factors inhibiting the stages of recognition of the MHA of the Sakai Bathin Sobanga Tribe. The research approach used is qualitative. This type of research is descriptive. The research location is in Bengkalis Regency, precisely in Duri City, Bathin Sobanga Village, Kesumbo Ampai District. The types and sources of data for this research are divided into primary and secondary data, primary data in the form of interview results and secondary data in the form of supporting data related to the stages of recognizing the existence of customary law communities. The results of the research regarding the stages of recognizing the existence of the traditional MHA of the Sakai Bathin Sobanga Tribe, Riau Province, were carried out through four stages, namely the identification, verification, validation and also the determination stages. The identification results contain data and information regarding fulfillment of the requirements used to carry out verification. Verification is a field inspection activity for the completeness and correctness of data and information resulting from identification. If there are no objections to the verification results, then the validation stage is carried out, namely an administrative completeness check for the validity of the verification results and stated in the validation report. Next, the determination stage is carried out. However, in the stage of recognizing the existence of the traditional MHA of the Sakai Bathin Sobanga Tribe, there were several obstacles and delays in the identification, verification, validation and also determination stages. Keywords: Sakai Bathin Sobanga Tribe, Minister of Home Affairs Regulation No. 52 of 2014, Recognition of the existence of MHA